1940
DOI: 10.1103/physrev.57.142
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Energy Constants of Dipolar Lattices

Abstract: In this paper, calculations are presented for the determination of the magnetic energy, assuming dipole-dipole interaction, of a macroscopic crystal possessing paramagnetic ions situated on a definite lattice, structure. Parallel and antiparallel configurations are considered as well as specimens of different shapes and lattice structures of various types. It is shown that the configuration of lowest energy cannot be strictly defined but is dependent upon the shape of the specimen. This configuration is an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1961
1961
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(21 citation statements)
references
References 3 publications
2
18
0
1
Order By: Relevance
“…Therefore, even if the ferromagnetic state may be more stable than the paramagnetic one, at least in the absence of demagnetizing field, it does not mean that another type of spin ordering is not more stable. Indeed, the magnetization is not the only factor in determining the local internal field as shown first by Sauer [22] who computed the energies of certain intuitively selected dipole arrays and found that ordered arrays of zero net magnetization (antiferromagnets) may have widely different energies, some of them lower than that due to the Lorentz field. The question then arose of identifying the actual magnetic order in the ground state of a pure dipole system for a given network (periodic or random) of moments (single-or multi-valued).…”
Section: The Mean-field Approximationmentioning
confidence: 99%
“…Therefore, even if the ferromagnetic state may be more stable than the paramagnetic one, at least in the absence of demagnetizing field, it does not mean that another type of spin ordering is not more stable. Indeed, the magnetization is not the only factor in determining the local internal field as shown first by Sauer [22] who computed the energies of certain intuitively selected dipole arrays and found that ordered arrays of zero net magnetization (antiferromagnets) may have widely different energies, some of them lower than that due to the Lorentz field. The question then arose of identifying the actual magnetic order in the ground state of a pure dipole system for a given network (periodic or random) of moments (single-or multi-valued).…”
Section: The Mean-field Approximationmentioning
confidence: 99%
“…The system we consider has the practical advantages of the high energy scale for spin-dependent phenomena (set by dipolar interactions) and the new physics associated with the longranged nature of the dipole interactions. Experimental realization of the system will give insight into several open questions in condensed matter physics including competition between ferro and antiferroelectric orders in crystals [19,20] and systems with frustrated spin interactions [21].…”
mentioning
confidence: 99%
“…In Paper I of this series, 47 we compared the dipolar and quadrupolar energy expressions against analytic expressions for ordered dipolar and quadrupolar arrays. 39,[60][61][62] In this work, we used the multipolar Ewald sum as a reference method for comparing energies, forces, and torques for molecular models that mimic disordered and ordered condensed-phase systems. The parameters used in the test cases are given in Table I.…”
Section: Methodsmentioning
confidence: 99%